2015
DOI: 10.1016/j.rpto.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of emotional intelligence on social-mental factors of human resource productivity

Abstract: Please cite this article in press as: Hakkak, M., et al. Investigating the effects of emotional intelligence on social-mental factors of human resource productivity. Journal of Work and Organizational Psychology (2015), http://dx. a b s t r a c tThis paper seeks to investigate the effects of emotional intelligence on social-mental factors of the human resource. Research population includes employees of 2 areas of Mellat Bank in Tehran province; 248 out of them were selected for data analysis. Bank employees ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 7 publications
1
9
0
2
Order By: Relevance
“…Focusing on university students, various studies [9,22,23] using self-report measures (TMMS), have found associations between the clarity and repair dimensions with higher levels of empathy, more satisfaction with life, and better quality in social relations. Similarly, studies have observed a relationship in adolescent students between high clarity and repair scores and higher scores for self-esteem, happiness, mental health, and life satisfaction, and lower scores for anxiety and depression [16,20,24]. If we consider attention, the association between this dimension with anxiety and depression is positive [9,15,16,25].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Focusing on university students, various studies [9,22,23] using self-report measures (TMMS), have found associations between the clarity and repair dimensions with higher levels of empathy, more satisfaction with life, and better quality in social relations. Similarly, studies have observed a relationship in adolescent students between high clarity and repair scores and higher scores for self-esteem, happiness, mental health, and life satisfaction, and lower scores for anxiety and depression [16,20,24]. If we consider attention, the association between this dimension with anxiety and depression is positive [9,15,16,25].…”
Section: Introductionmentioning
confidence: 92%
“…These components are directed at identifying and reflecting on emotions (attention), understanding one’s own emotional states (clarity) and, finally, repairing negative feelings (repair). The literature generally shows that subjects with higher EI (evaluated using the TMMS) report fewer physical symptoms, less social anxiety and depression, better self-esteem, greater interpersonal satisfaction, and more use of active coping strategies for solving problems [15,16,17]. Nonetheless, the involvement of each of the dimensions that comprise EI has a different weighting depending on the construct to which it relates [18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Palmer & Gignac (2012) found that emotionally intelligent leadership was correlated with employee engagement. Moreover, Hakkak, Nazarpoori, Mousavi & Ghodsi. (2015) found that emotional intelligence has a positive effect on social-mental factors of human resources.…”
Section: Talent Management and Emotional Intelligencementioning
confidence: 99%
“…Therefore, the area of cognition and emotion is emphasized as a basic structure in human perception and psyche. In this way, emotional intelligence can solve at least a part of problems originated from failure in understanding human behavior and social mutual relationships [10][11][12][13]. Some professionals in mental health have expressed that the contemporary world has become so unstable and uncertain that it is difficult to find a way for coping with it.…”
Section: Introductionmentioning
confidence: 99%